Respuesta :
y = x + 8
y= 3x - 11
u would multiply y = x + 8 by -3 to eliminate the x's
y= 3x - 11
u would multiply y = x + 8 by -3 to eliminate the x's
Answer:
The equation y=x+8 has to be multiplied by -3 to eliminate x .
Step-by-step explanation:
The given equations are :
y = x + 8 and y = 3x − 11.
The equations can be written as:
x-y=-8 and 3x-y=11.
To solve the equation by elimination we make the coefficients same with opposite sign and then add.This way the variable is elminated.
The coefficients of x are 1 and 3 .To eliminate the variable x we multiply equation y=x+8 or x-y=-8 by -3 .